APPROACHES TO DETERMINING THE EFFECTIVENESS OF BUSINESS COMMUNICATION IN THE PREPARATION OF STUDENTS - O. N. Gromova (Вестник университета)
The issues of the effectiveness of communication as one of the key factors in the formation of students for successful activity in the organization have been considered. It has been shown, that the concept of efficiency is a nonlinear problem, supposing the determination of the compromise zone for each of the parties involved. It has been revealed, that different forms of communication assume the use of appropriate criteria for determining their effectiveness. The significance of each form of communication for improving the efficiency of communication in General, the process of training students, has been disclosed.